THE INFLUENCE OF ENGLISH ON NATIONAL LANGUAGES IN THE ERA OF GLOBALIZATION - Akhmedova Nodira Djavadullayevna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Looking into how English shapes local tongues during global shifts defines this piece. Instead of just borrowing words, shifts in grammar appear alongside cultural shifts tied to English spread. Vocabulary gains from English often come with structural adjustments over time. While some welcome added convenience, others fear loss of traditional expression. Identity ties to language may strengthen or weaken depending on usage patterns. Outcomes vary widely across regions and linguistic traditions involved.